DAMPAK PENGGUNAAN JENIS PAKAN YANG BERBEDA TERHADAP LAJU PERTUMBUHAN BENIH IKAN PATIN (PANGASIUS HYPOPHTHALMUS) - Alissa Qothrunnada; Chandra Adi Prabowo (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study investigates the effect of different fish feed types on the growth rate of Pangasius sp. The experiment was carried out on Pangasius sp. with a size of 6-8 cm for 28 days. This study uses a randomized design with three different treatments and four repetitions. The treatments include a mix of the pellet feed, kale flour, and only kale flour feed. The results showed that different feed types substantially influenced Pangasius sp. growth in terms of weight and length. The ideal water temperature for Pangasius sp. to grow and develop is 27-29 °C. On the other hand, the optimum temperature was between 24-27 °C for the treatment of pellets and kale flour. The pH levels during the treatment in this study ranged between 7.2 and 8.1.